Radiotoxicity of alpha particles versus high and low energy electrons in hypoxic cancer cells - Maucksch, Ute; Runge, Roswitha; Oehme, Liane; Kotzerke, Jörg; Freudenberg, Robert (Nuklearmedizin - NuclearMedicine, 2018)
Purpose: Hypoxic regions of tumors are less sensitive to radio- and chemotherapy, leading to poor prognosis of patients. One option to overcome the radioresistance is the irradiation of hypoxic tumors with high linear energy transfer (LET) α- or Auger electronemitters assuming their radiotoxicity would be less dependent on the cellular oxygenation status. Therefore, the aim of the present study was to determine whether irradiation with the intracellularly distributed Auger electron/γ-emitter 99mTc using the tracer [99mTc]TcHMPAO is a promising therapeutic option for the treatment of hypoxic tumor cells. Thus, the high LET α-particleemitter 223Ra ([223Ra]RaCl2) and the low LET β-emitter 188Re ([188Re]NaReO4) were studied in comparison to [99mTc]Tc-HMPAO. Materials and methods: A431 tumor cells were incubated with [99mTc]Tc-HMPAO (1–20 MBq/2 mL), [223Ra]RaCl2 (1.4–16.3 kBq/2 mL) or [188Re]NaReO4 (0.3–13.7 MBq/2 mL) under normoxic or hypoxic conditions. The degree of radiotoxicity was analyzed using the colony forming assay (CFA), and the intracellular radionuclide uptake of the radiotracers was quantified. Results: Hypoxic A431 cells are less radiosensitive to irradiation with [99mTc]Tc-HMPAO or [188Re]NaReO4 than normoxic ones. In contrast, the radiosensitivity of A431 cells is almost independent of the oxygen status when treated with the [223Ra]RaCl2. Conclusions: We demonstrate that the Auger electron/γ-emitter 99mTc ([99mTc]Tc-HMPAO), which does not bound directly to the DNA, is not a promising therapeutic option for hypoxic tumor cells. But the high LET α-particle-emitter 223Ra is more suitable for the treatment of hypoxic tumor cells than irradiation with [99mTc]Tc-HMPAO or the low LET bemitter 188Re.Zielsetzung: Hypoxische Tumorregionen sind bei Radio- und Chemotherapie weniger sensitiv als Tumorregionen mit ausreichender Sauerstoffversorgung. Dies verursacht eine schlechte Prognose für Tumorpatienten. Eine Option die Radioresistenz zu überwinden, stellt die Bestrahlung mit α-Partikel-Emittern oder Auger-Elektronen-Emittern mit einem hohen linearen Energietransfer (LET) dar. In dieser Studie soll untersucht werden, ob die Bestrahlung von hypoxischen Tumorzellen mit dem intrazellulär aufgenommenen γ- sowie Auger-Elektronen-Emitter 99mTc unter Verwendung des Radiotracers [99mTc]Tc-HMPAO eine vielversprechende Therapieoption darstellen könnte. Vergleichend wurde der Hoch-LET α-Partikel-Emitter 223Ra ([223Ra]RaCl2) und der Niedrig-LET β-Emitter 188Re ([188Re]NaReO4) eingesetzt. Methoden: A431 Tumorzellen wurden unter normoxischen oder hypoxischen Kulturbedingungen mit [99mTc]Tc-HMPAO (1–20 MBq/2 ml), [223Ra]RaCl2 (1,4–16,3 kBq/2 ml) und [188Re]NaReO4 (0,3–13,7 MBq/2 ml) inkubiert. Zur Detektion der resultierenden strahlenbiologischen Wirkung wurde der Koloniebildungsassay angewendet. Zusätzlich wurde die intrazelluläre Aufnahme der Radiotracer quantifiziert. Ergebnisse: Nach Inkubation von [99mTc]Tc-HMPAO sind hypoxische A431-Zellen weniger strahlensensitiv als normoxische Zellen. Im Gegensatz zur Behandlung mit [99mTc]Tc-HMPAO oder [188Re]NaReO4 wurde bei Behandlung mit [223Ra]RaCl2 ein geringerer Einfluss des Sauerstoffstatus auf die Radiosensitivität von A431-Zellen gefunden. Schlussfolgerung: Damit konnte gezeigt werden, dass der nicht direkt an die DNA gebundene Auger-Elektronen-/ γ-Emitter 99mTc ([99mTc]Tc-HMPAO) die Radioresistenz von hypoxischen Tumorzellen nicht überwinden kann. Jedoch stellt der Hoch-LET α-Partikel-Emitter 223Ra ([223Ra]RaCl2) eine bessere Behandlungsoption dar.
Keywords: Hypoxia; [99mTc]Tc-HMPAO; [188Re]NaReO4; [223Ra]RaCl2; cellular survival; radiotoxicity